Intestinal Flora as a Potential Strategy to Fight SARS-CoV-2 Infection - He, Li-Hong; Ren, Long-Fei; Li, Jun-Feng; Wu, Yong-Na; Li, Xun; Zhang, Lei (Frontiers in Microbiology, 2020)
The novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus formerly known as 2019-nCoV, has spread rapidly worldwide. In addition to the typical symptoms of lung infection, some patients with COVID-19 also have digestive tract symptoms. Further, SARS-CoV-2 has been isolated from the feces of some patients, suggesting that the virus may infect the intestinal tract and lead to intestinal flora disorders. However, the intestinal flora has been proved to be closely related to metabolism, inflammation, and immune homeostasis of the host. Subsequent studies found that the intestinal flora played a key role in the pulmonary immune and inflammatory activation of the host. This review aimed to explore the potential strategies to prevent and treat SARS-CoV-2 infection by targeting the intestinal flora. The negative effects of SARS-CoV-2 on host intestinal microecology and the critical role of the intestinal flora during airway infectious diseases were highlighted. Particularly, the study focused on the important function and mechanism of the “gut-lung axis.”